Examining the “customer” metaphor in hospitals : a case study of Singapore - Eng, Casie Pei Shi (2010)
In a competitive society, marketing is done by organisations in order to differentiate themselves from the multitudes of offerings available to the masses. Every day we are bombarded by advertising messages at every corner. It has become so prevalent that even social institutions see the need to market in order to survive. In doing so, have they ignored their social responsibilities and focused on only profit making, treating them as customers more than their users? Or have they embraced the customer metaphor, and improved in their treatment of their users? Research has been done in the US (Hutton, 2005) examining the marketing techniques of social intuitions and how they have veered from their responsibilities. However, there is little to no research available in Singapore. Hence, this study examines the customer metaphor in hospitals and its acceptability, through surveys, focus groups, and textual analysis of news articles and advertisements related to hospital marketing from 2006 to 2009. Our findings show that the customer metaphor has indeed been embraced by hospitals, more so in private hospitals than in public hospitals. This has had a positive effect, resulting in better service and an increase in customer satisfaction: a win-win situation for both parties.